Inconsistent effects of gluten on obesity: is there a role for the haptoglobin isoforms?. (December 2020) - Silva, Rachel B.; Rodrigues, Érica; Coelho, Bruna S.; Andrade, Karine; Fonseca, Luana; Fernandes-Braga, W.; Ferreira, A.; Shivappa, N.; Hébert, J.R.; Silvestre, Simone CM.; Fasano, A.; Freire, Rachel H.; et al.
Summary: Background and aims: There is no clear evidence about the effects of gluten intake on obesity. It is known that gluten's effects on gut permeability are mediated by zonulin, a protein identified as pre-haptoglobin 2, a physiological regulator of the intestinal barrier. We investigated the obesogenic and inflammatory effects of gluten and its association with the haptoglobin genotype. Methods: This was a single blinded, crossover study, including 40 overweight or obesity women free of celiac disease. Participants adopted a gluten-free diet (GFD) for 8 weeks and consumed a gluten-free muffin (GF-M) or a gluten-containing muffin (GLU-M, 24 g gluten) for 4 weeks, switching muffin type during the subsequent 4 weeks. During a follow-up period of 4 weeks we evaluated the usual diet (UD). Food diaries were collected to estimate the macronutrient intake and dietary inflammatory index (DII®). Bodyweight and composition, resting energy expenditure (REE), and cytokines were assessed. Haptoglobin alleles (Hp1 and Hp2) were genotyped to characterize zonulin expression. Results: Energy and macronutrient intakes were similar during both periods, except for protein intake, which was higher during GLU-M. DII scores indicated a more inflammatory profile during the GF-M and GLU-M periods compared to UD. No differences were observed in body composition or REE between interventions when the Hp genotype was not considered. Nonetheless, those carrying the Hp2-2 genotype (overexpressing zonulin) presented lower REE and higher levels of IL6 and IL1beta only during gluten intake (GLU-M and UD) compared to age- and body mass index-matched Hp1-1 carrier. These results suggest an obesogenic and inflammatory action of gluten only in those overexpressing zonulin (Hp2-2). Conclusion: These results highlight the importance of zonulin as the mediator of gluten obesogenic and inflammatory effects. Our data suggest that in the presence of gluten, zonulin release is associated with a reduction of REE and an increase of inflammatory markers that are not seen in zonulin low producers. Graphical abstract: Image 1 Highlights: Gluten intake has no impact on body weight, body composition or resting energy expenditure. Gluten-free diet has a higher inflammatory potential due to exclusion of some micronutrients. Hp2 allele carriers has a higher IL6 and IL1β when eating gluten than Hp1 carriers. Hp2 allele carriers has a lower resting energy expenditure when eating gluten than Hp1 carriers. Zonulin production is a potential field of investigation regarding metabolic effect of gluten.